Anti-nociceptive and Anti-inflammatory Activities of Asparacosin A Involve Selective Cyclooxygenase 2 and Inflammatory Cytokines Inhibition: An in-vitro, in-vivo, and in-silico Approach - Karim, Nasiara; Khan, Inamullah; Khan, Waheed; Khan, Imran; Khan, Ajmal; Halim, Sobia Ahsan; Khan, Hizbullah; Hussain, Javid; Al-Harrasi, Ahmed (Frontiers in Immunology, 2019)
Triterpenes possess anti-inflammatory and anti-nociceptive effects. In this study anti-inflammatory activities of Asparacosin A were evaluated` using in-vitro cyclooxygenases 1 and 2 (COX-1/2) inhibition assays. Moreover anti-nociceptive activities were assessed in-vivo by carrageenan-induced paw edema test, xylene-induced ear edema tests, and acetic acid-induced writhing and formalin tests. Additionally molecular docking was conducted to elucidate the binding mechanism of the compound and to correlate the in-vitro findings with the in-silico data. Oral administration of Asparacosin A at the doses of 10, 20 and 40mg/kg induced significant anti-inflammatory effects (*p<0.05, **p<0.01 and ***p<0.001) in a dose-dependent manner in both models. Asparacosin A also inhibited the human recombinant COX-2 enzyme and caused a dose-dependent decrease in the levels of TNF-α, IL-1β, and PGE2 in the carrageenan-induced paws. Moreover Asparacosin A displayed significant anti-nociceptive effects (*p< 0.05, **p< 0.01, ***p< 0.001) at the doses of 10, 20 and 40 mg/kg in acetic-acid induced writhing test. However in formalin test, Asparacosin A (10-40 mg/kg, p.o) produced anti-nociceptive effects only in the late phase, similar to the effect observed with the reference drug celecoxib (50 mg/kg, p.o). Molecular docking was carried out on both COX-1 and COX-2 structures which revealed that Asparacosin A targets allosteric binding site similar to the binding mode of the selective COX inhibitor. In conclusion, Asparacosin A exhibits anti-inflammatory and peripheral antinociceptive activities which are likely mediated via inhibition of COX-2 enzyme and inflammatory cytokines. Furthermore, Asparacosin A can serve as a model to obtain new and more selective potent anti-inflammatory and antinociceptive drugs.